2002
DOI: 10.1090/s0002-9947-02-03114-8
|View full text |Cite
|
Sign up to set email alerts
|

On the nonexistence of closed timelike geodesics in flat Lorentz 2-step nilmanifolds

Abstract: Abstract. The main purpose of this paper is to prove that there are no closed timelike geodesics in a (compact or noncompact) flat Lorentz 2-step nilmanifold N/Γ, where N is a simply connected 2-step nilpotent Lie group with a flat left-invariant Lorentz metric, and Γ a discrete subgroup of N acting on N by left translations. For this purpose, we shall first show that if N is a 2-step nilpotent Lie group endowed with a flat left-invariant Lorentz metric g, then the restriction of g to the center Z of N is dege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…Let (g, , ) be a flat pseudo-Euclidean 2-step nilpotent Lie algebra. In [7], the author showed that if the metric , is Lorentzian, then g is an extension trivial of H 3 , where H 3 is a 3-dimensional Heisenberg Lie algebra. Let us studies some properties of (g, , ) in other signatures.…”
Section: Flat Pseudo-euclidean 2-step Nilpotent Lie Algebrasmentioning
confidence: 99%
See 1 more Smart Citation
“…Let (g, , ) be a flat pseudo-Euclidean 2-step nilpotent Lie algebra. In [7], the author showed that if the metric , is Lorentzian, then g is an extension trivial of H 3 , where H 3 is a 3-dimensional Heisenberg Lie algebra. Let us studies some properties of (g, , ) in other signatures.…”
Section: Flat Pseudo-euclidean 2-step Nilpotent Lie Algebrasmentioning
confidence: 99%
“…3. Guédiri showed in [7] that a flat Lorentzian 2-step nilpotent Lie algebra is a trivial extension of the 3-dimensional Heisenberg Lie algebra H 3 . 4.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Guediri has proved that compact flat spacetimes contain a causal periodic geodesic [14], and that such spacetimes contain a periodic timelike geodesic if and only if the fundamental group of the underlying manifold contains a nontrivial timelike translation [15]. Non existence results for periodic causal geodesics are also available, see [12,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The existence of closed timelike geodesic has been established also by Galloway in [14], where the author proves the existence of a longest closed timelike curve, which is necessarily a geodesic, in each stable free timelike homotopy class. Also non existence results for nonspacelike geodesics are available, see [15,29].…”
Section: Introductionmentioning
confidence: 99%